Retaining Wall Reinforcement of Road Hill Slope of Selacau-Lagadar, West Bandung: A Case Study - Agustian, Yanyan; Setiawan, Asep; Herdian Bayu AshSiddiq, Raden (International Journal of Psychosocial Rehabilitation, 2020)
The problem that is often found in areas with high rainfall is frequent landslides. Various methods are carried out by giving strength to the soil so that deformation does not occur like an artificial or natural slope. Selacau-lagadar road in West Bandung is located in an area with steep cliffs and frequent landslides. This study was conducted to evaluate the use of cantilever concrete wall retaining walls to overcome landslides in the cut-down roads of the Selacau -adar road in West Bandung. Soil properties obtained from field investigation and laboratory experiments were used as parameters in determining the design of the retaining wall. The calculation results show that based on the soil properties, the chosen retaining wall, the type of cantilever concrete wall, is the desired safety factor if viewed from three factors, namely: the resistance to overturning, sliding and bearing capacity of the soil where the retaining wall will constructed.